Improvement of self-organizing time divison multiple access in vehicular ad-hoc networks - Arif, Ari Sabir (2014)
Vehicular ad-hoc network (VANET) is a subclass of mobile ad-hoc network (MANET) with the key difference of frequently changing mobility pattern and network topology. It can provide both vehicle-to-vehicle (V2V) and vehicle-toinfrastructure (V2I) communications thereby can greatly improve the safety and efficiency of road traffic. Media Access Control (MAC) is one of the key protocols for VANET in providing real-time services. Self-Organized Time Division Multiple Access (STDMA) is one of the MAC protocols for VANETs. The main problem of STDMA (MAC) protocol is delay. In this research, we proposed a scheduling algorithm to surmount this delay and improve the performance of STDMA MAC protocol, by allocating additional time slots for all nodes in the emergency service category. In the proposed algorithm we divide the available bandwidth between two different service classes: best effort and real time. There are two different counters, which count the number of allocated slots to users of different classes. The highway scenario is selected to model the vehicle traffic patterns. Simulation results show that for different number of nodes the proposed scheme has improved the delay by 23% and throughput by 4% compared to STDMA. For different values of speed it has shown 24% lower delay and 23% higher throughput than STDMA. In addition, result show that our proposed protocol outperforms the conventional one CSMA/CA in terms of delay and throughput